2020
DOI: 10.3390/ijerph17249431
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Physical Activity during School Closures Imposed by the First Wave of the COVID-19 Pandemic: Physical Education Teachers’ Behaviors in France, Italy and Turkey

Abstract: The COVID-19 pandemic has drastically reduced physical activity (PA) behaviors of many people. Physical education (PE) is considered one of the privileged instruments to promote youths’ PA. We aimed to investigate the effects of lockdown on PE teachers’ behaviors promoting their students’ out-of-school PA and differences between three European countries. A sample of 1146 PE teachers (59.5% females) from France, Italy, and Turkey answered an online questionnaire about guiding students to engage in out-of-school… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 43 publications
3
53
0
1
Order By: Relevance
“…According to Bandura [14], self-efficacy could be influenced by the workplace environments, especially with supervisors' verbal persuasion and modeling serving as important prompts to workers' self-efficacy development, also among teachers. In the case of our participants, a context-specific lack of guidelines for goal-directed activities from the Italian Ministry of Education was reported in a previous study [7]; teachers received only general indications for online teaching while lacking support for the delivery of practical subjects such as PE. Another possible explanation regards the support offered by PE coaches in primary schools, reported as a context-specific factor influencing teachers' feeling of competence and confidence to deliver PE or promote active play [40].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…According to Bandura [14], self-efficacy could be influenced by the workplace environments, especially with supervisors' verbal persuasion and modeling serving as important prompts to workers' self-efficacy development, also among teachers. In the case of our participants, a context-specific lack of guidelines for goal-directed activities from the Italian Ministry of Education was reported in a previous study [7]; teachers received only general indications for online teaching while lacking support for the delivery of practical subjects such as PE. Another possible explanation regards the support offered by PE coaches in primary schools, reported as a context-specific factor influencing teachers' feeling of competence and confidence to deliver PE or promote active play [40].…”
Section: Discussionmentioning
confidence: 78%
“…Within the school closure, teaching PE confronted teachers with an unprecedented challenge, while also struggling with the lack of governmental guidance and concerns related to COVID-19 pandemic consequences. Teachers needed to radically transform the discipline contents, methodologies, practices, and communication strategies [7]. For instance, Italian secondary school PE teachers provided their pedagogical contents increasing the use of digital technologies (e.g., live streaming classes or video tutorials) and renovating the pedagogical formats used in their classes to promote students' out-of-school physical activity (PA) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this background, most European countries have wondered about the ways of promoting of physical education. Concerning that, there has been resistance on a normative and organizational plane, above all linked to qualification of teachers [71], which becomes, now more than ever, an essential promotion strategy which shall be revised periodically. Fortunately, in some European countries the training of teachers has been implemented [27].…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions Gobbi et al (2020) suggested that the COVID-19 pandemic is "an opportunity to restore the role of PE in youths' lives," by meaningfully promoting PA as an extension of the home environment. The widespread use of PE, PA, and nutrition resources provided to educators, parents, and students during the COVID-19 quarantine via the #HealthyKidsQuarantined campaign largely supports this notion.…”
Section: Limitationsmentioning
confidence: 99%